Excess of glucocorticoids during late gestation impairs the recovery of offspring's β‐cell function after a postnatal injury. Issue 8 (29th July 2021) - dos Santos, Cristiane; Rafacho, Alex; Ferreira, Sandra Mara; Vettorazzi, Jean Franciesco; dos Reis Araújo, Thiago; Mateus Gonçalves, Luciana; Ruhrmann, Sabrina; Bacos, Karl; Ling, Charlotte; Boschero, Antônio Carlos; Jorge dos Santos, Gustavo
Abstract: Since prenatal glucocorticoids (GC) excess increases the risk of metabolic dysfunctions in the offspring and its effect on β‐cell recovery capacity remains unknown we investigated these aspects in offspring from mice treated with dexamethasone (DEX) in the late pregnancy. Half of the pups were treated with streptozotocin (STZ) on the sixth postnatal day (PN). Functional and molecular analyses were performed in male offspring on PN25 and PN225. Prenatal DEX treatment resulted in low birth weight. At PN25, both the STZ‐treated offspring developed hyperglycemia and had lower β‐cell mass, in parallel with higher α‐cell mass and glucose intolerance, with no impact of prenatal DEX on such parameters. At PN225, the β‐cell mass was partially recovered in the STZ‐treated mice, but they remained glucose‐intolerant, irrespective of being insulin sensitive. Prenatal exposition to DEX predisposed adult offspring to sustained hyperglycemia and perturbed islet function (lower insulin and higher glucagon response to glucose) in parallel with exacerbated glucose intolerance. β‐cell‐specific knockdown of the Hnf4α in mice from the DS group resulted in exacerbated glucose intolerance. We conclude that high GC exposure during the prenatal period exacerbates the metabolic dysfunctions in adult life of mice exposed to STZ early in life, resulting in a lesser ability to recover the islets' function over time. This study alerts to the importance of proper management of exogenous GCs during pregnancy and a healthy postnatal lifestyle since the combination of adverse factors during the prenatal and postnatal period accentuates the predisposition to metabolic disorders in adult life.